2021
DOI: 10.24193/adn.14.2.18
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Integrated Mathematics Lessons with Children’s Literature on the Fifth Grade Students’ Place Value Understanding

Abstract: The comprehension of the place value concept which is based on the grouping of numbers in accordance with distinct systems is not so easy. One of the sources that may contribute to the comprehension of the place value and making connections with daily life is children’s books. The effects of several tools on the comprehension of the place value have been analyzed in the literature, but the effects of children’s books in this regard have not been so frequent. Therefore, the aim of the study is to analyze the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…A total of 11 studies (Björklund & Palmér, 2020, 2022; Can et al, 2020; Capraro & Capraro, 2006; den Heuvel‐Panhuizen et al, 2009; Durmaz & Miçooğullari, 2021; Edelman, 2017; Ompok et al, 2018; Rathé et al, 2018; Van den Heuvel‐Panhuizen & Elia, 2011; Wikholm & Aerila, 2017) presented different approaches to the use of picture books in mathematics instruction. The findings across these studies revealed that most teachers used picture books during the introductory and practical parts of mathematics lessons (Can et al, 2020; Edelman, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 studies (Björklund & Palmér, 2020, 2022; Can et al, 2020; Capraro & Capraro, 2006; den Heuvel‐Panhuizen et al, 2009; Durmaz & Miçooğullari, 2021; Edelman, 2017; Ompok et al, 2018; Rathé et al, 2018; Van den Heuvel‐Panhuizen & Elia, 2011; Wikholm & Aerila, 2017) presented different approaches to the use of picture books in mathematics instruction. The findings across these studies revealed that most teachers used picture books during the introductory and practical parts of mathematics lessons (Can et al, 2020; Edelman, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…After that, some teachers would provide mathematical guidance to the students, such as posing open‐ended questions to ease and deepen their understanding (Björklund & Palmér, 2020; den Heuvel‐Panhuizen et al, 2009; Van den Heuvel‐Panhuizen & Elia, 2011). In other words, the picture book stories not only act as new teaching content to motivate students (Wikholm & Aerila, 2017), but also pave the way for students to further develop their mathematical concepts or skills (Durmaz & Miçooğullari, 2021). By allowing students to read the picture books aloud, they could learn how to learn mathematical knowledge independently, thus benefiting their learning at a later stage (Can et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mathematics teaching and children's literature integration, where language-related skills such as reading are employed, are one of the approaches that can be used for this purpose. Because research shows that integrated mathematics courses have a positive effect on mathematics success (Boebinger, 2015;Durmaz & Miçooğulları, 2021;Green, 2013;Lemonidis & Kaiafa, 2019;Munro, 2013;Stone, 2016;Thomas & Feng, 2015), literary success (Boebinger, 2015), geometry success/skills (Capraro & Capraro, 2006;Hong, 1996), interest/motivation in mathematics (Hong, 1996;Jennings et al, 1992;Mink & Fraser, 2005), attitude towards mathematics (Munro, 2013), problem-solving (Cankoy, 2011;Lynch, 2006), critical thinking, procedural-conceptual knowledge (Huffman, 2012), using mathematics in daily life (Moore, 2008;Munro, 2013;Young, 2001), behavioral problems (Whitney, 2011), and reducing mathematical anxiety (Green, 2013). However, some studies have also found that such integration has no effect on some issues such as attitudes towards problems (White, 2003), mathematical success (Hassinger-Das et al, 2015), attitude towards mathematics (Stone, 2016), and reducing of behavioral disorders (Whitney et al, 2017).…”
Section: Introductionmentioning
confidence: 99%